Age Distributions and the Current Account -A Changing Relation? - Thomas Lindh; Bo Malmberg (Uppsala University, Department of Economics, 1999)
In recent research age distribution effects on the current account have been found in cross-country panel regressions. The reason is different effects on saving and investment from cohort-size variation. In a panel of annual OECD data 1960-1995, we find that the age effects on saving are similar to results on world samples but the effects on investment are very different. The respective age profiles of saving and investment are much more similar in the OECD sample. This may be one factor accounting for the home-country bias found in international capital markets. Disaggregating investment we find that young cohorts have a positive correlation with housing investment while older but still active cohorts have a positive correlation with business investment. The differences in saving and investment effects are, nevertheless, sufficient to generate persistent and sizeable age effects on the current account. Our results suggest that policies concerning current account balance should take into consideration age distributions and the degree of development.
urn:nbn:se:uu:diva-2464
Keywords: E20; J10; O57; 330; age distribution; home-country bias; saving; investment; current account; OECD; Leistungsbilanz; Bevölkerungsstruktur; OECD-Staaten